Warfare in the far north. - Historical Division, Special Staff, United States Army; Erfurth, Waldemar (1947)
Outline: inexperience of the German soldier in the Arctic; the climate in the far north; terrain in the Finnish Karelian region; demands of the war theater on the troops; the new Finnish frontiers change the strategic situation in the far north of Europe; and future prospects. Contains one map of the Finnish-Russian border area (situation at the end of 1941 with the German and Finnish fronts).